Epidemiology of injuries in young Spanish soccer players according to the playing positions (Epidemiología de las lesiones en futbolistas jóvenes españoles según la demarcación) - Chena Sinovas, Marcos; Rodríguez Hernández, María Luisa; Bores Cerezal, Antonio (Retos, 2020)
Abstract. Soccer is a complex sport that involves relatively high risks of injury. The high participation rates in soccer has increased the soccer-related injuries among the youth population. There are different physiological demands between playing positions, however a limited amount of studies about the incidence of injuries in soccer players of differing ages and playing position has been published. The aim of this study was to identify the incidence, type, location and severity of injuries in young Spanish soccer players according to playing position in different age groups. There were 431 participants who were male soccer players between the ages of 7 and 23 and they were studied for a full season. All players were classified according to individual playing position: goalkeepers, external defenders, central defenders, central midfielders, external midfielders and forwards; and according to age groups: younger than or equal to 9 years, younger than or equal to 11 years, younger than or equal to 13 years, younger than or equal to 15 years, younger than or equal to 18 years, and younger than or equal to 23 years. Incidence of the typology, location and severity of injuries according to playing position for each to the age groups was different. Injury incidence demonstrated a growth trend according to age. Forwards sustained an incidence of injuries significantly greater compared with goalkeepers, central defenders, external defenders and external midfielders. In conclusion, injuries constitute a health threat. Knowledge of the epidemiology of injuries in young soccer players is very important in order to be able to develop appropriate preventive measures according to age groups and playing positions. Resumen. El fútbol es un deporte complejo que implica relativamente un alto riesgo de lesión. La alta tasa de participación en el fútbol ha aumentado el número de lesiones entre la población juvenil. Existen diferencias en las demandas fisiológicas según la demarcación de los jugadores sobre el terreno de juego, sin embargo, se ha publicado una cantidad limitada de estudios sobre la incidencia de lesiones en jugadores de fútbol de diferentes edades y la demarcación. El objetivo de este estudio fue identificar la incidencia, la tipología, la localización y la severidad de las lesiones en futbolistas españoles jóvenes atendiendo a la demarcación sobre el terreno de juego en los diferentes grupos de edad. Participaron 431 futbolistas masculinos entre las edades de 7 y 23 años, los cuales fueron estudiados durante una temporada completa. Todos los jugadores fueron clasificados según su demarcación sobre el juego: porteros, defensas laterales, defensas centrales, mediocentros, centrocampistas externos y delanteros; y según grupos de edad: menores de 9 años, menores de 11 años, menores de 13 años, menores de 15 años, menores de 18 años, y menor de 23 años. La incidencia de la tipología, localización y severidad de las lesiones según la demarcación de los jugadores en cada grupo de edad fue diferente. Los delanteros sufrieron una incidencia de lesiones significativamente mayor en comparación con los porteros, defensas centrales, defensas laterales y centrocampistas externos. En conclusión, las lesiones constituyen una amenaza para la salud. El conocimiento de la epidemiología de las lesiones en futbolistas jóvenes es muy importante para poder desarrollar medidas preventivas apropiadas de acuerdo con las diferentes edades y según la demarcación sobre el terreno de juego.